BORON ISOTOPE GEOCHEMISTRY OF PALEOZOIC BRACHIOPOD CALCITE: IMPLICATIONS FOR A SECULAR CHANGE IN THE BORON ISOTOPE GEOCHEMISTRY OF SEAWATER OVER THE PHANEROZOIC - Joachimski M.M.; Simon L.; van Geldern R.; L?cuyer C. (My University, 2005)
Boron isotope composition of marine carbonates has been proposed as a paleo-pH proxy and potential tool to reconstruct atmospheric pCO2. The precise knowledge of the boron isotopic composition of ancient seawater represents the fundamental prerequisite for any paleo-pH reconstruction. This contribution presents boron isotope values for Silurian to Permian brachiopod calcite that might be used to reconstruct pH or boron isotope composition of past oceans. All brachiopod shells were screened for diagenetic recrystallization by means of cathodoluminescence microscopy, trace element geochemistry (B, Fe, Mn, Sr) as well as SEM. Only nonluminescent shells revealing well-preserved microstructures, high strontium and boron concentrations as well as low iron and manganese contents were accepted for boron isotope analysis. The boron isotope ratios of Silurian, Devonian, Pennsylvanian and Permian brachiopod calcite range from 6.8 to 11.0‰, 7.3 to 14.9‰, 12.4 to 15.8‰ and 10.1 to 11.7‰, respectively. These δ11B values are significantly lower in comparison to δ11B values of modern biogenic carbonates and indicate that the Paleozoic oceans were depleted in 11B by up to 10‰. Box modeling of the boron geochemical cycle suggests that the significant depletion of 11B in the oceanic reservoir may have been initiated by an enhanced continental boron discharge. Our data support the earlier made conclusion that boron isotopes may not be used in the geological past as reliable paleo-pH proxy unless the boron isotopic composition of ancient oceans can be constrained by further studies.
Keywords: Paleozoic; Paleozoic